Cloud Computing Awareness in Malaysia Construction industry - Kai, Chen Goh; Kamalludin, Bin Bilal; Hui, Hwang Goh; Sulzakimin, Mohamed; Chang, Saar Chai; Gui, Hun Chuen (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The construction industry has been treated by fragmentation, lack of integration and complexities in processes and activities which could ultimately bring a negative impact to the construction project success. Therefore, collaboration is very important with the purpose to improve the productivity and effectiveness of construction management and to ensure the efficient utilization of resources. Cloud computing is the latest technology which has acted as a platform to support access to applications, information and services by using only an internet connection. However, it is doubt that the construction stakeholders are aware and use the cloud computing. Thus, the purpose of this research is to determine the awareness of cloud computing and identify the reasons of engagement with cloud computing in Malaysia construction industry. This research was focused on the main contractors within Johore Bahru only. In this research, the research method used quantitative approach and descriptive analysis includes frequency analysis and mean score to interpret the data. From the finding of the research, the Malaysian construction professions have the awareness on cloud computing. However, their level of knowledge is at low level. The concept of cloud computing is still new and it is still in the infant stage of its development in Malaysia construction industry.